Human Development and Institutional Quality: Enhancing Welfare in OIC Countries - Basri; Riska Prasasti; Muh. Irnandas; Hasnidar Yuslin; Sitti Nikmah Marzuki (Journal of Development Economic and Social Studies, 2026)
This study investigates the factors influencing human resource development (HRD) in Organization of Islamic Cooperation (OIC) countries, focusing on the moderating role of government governance. The analysis explores variables such as inflation, foreign direct investment (FDI), GDP, population, unemployment, international trade, and human capital, examining their impact on HRD and institutional quality. Secondary data from trusted sources including the World Bank, UNDP, Our World in Data, and WGI is utilized, covering 50 OIC countries from 2012 to 2021. The research applies Dynamic Panel GMM and Moderated Regression Analysis (MRA) to identify relationships and moderating effects. Findings show that inflation adversely affects the Human Development Index (HDI), while FDI and economic growth positively influence HDI, highlighting the importance of foreign investment in revitalizing OIC economies. Population growth, human capital, and unemployment also play crucial roles in HRD. Furthermore, government governance emerges as a quasi-moderator, underlining its significance in the effective development of human resources. This study emphasizes the importance of addressing inflation, FDI, GDP, unemployment, human capital, and trade policies to foster sustainable HRD, with government governance playing a key supportive role.